2011
DOI: 10.1016/j.neuroimage.2011.05.053
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of voxel and surface based cortical thickness estimation methods

Abstract: Cortical thickness estimation performed in-vivo via magnetic resonance imaging is an important technique for the diagnosis and understanding of the progression of neurodegenerative diseases. Currently, two different computational paradigms exist, with methods generally classified as either surface or voxel-based. This paper provides a much needed comparison of the surface-based method FreeSurfer and two voxel-based methods using clinical data. We test the effects of computing regional statistics using two diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
144
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(154 citation statements)
references
References 68 publications
(125 reference statements)
5
144
1
4
Order By: Relevance
“…32 The amount of thinning observed in our patients (approximately 2%-5% in 6 months) is beyond reported atrophy rates for community-dwelling elderly 33 and comparable to the thickness decline in patients with Alzheimer disease. 34 In the current study, we found no association between remote changes in cortex or connecting fiber tracts and clinical outcome (supplementary results, table e-2). This might relate to several factors.…”
Section: Figure 4 Influence Of Infarct Cavitationcontrasting
confidence: 51%
“…32 The amount of thinning observed in our patients (approximately 2%-5% in 6 months) is beyond reported atrophy rates for community-dwelling elderly 33 and comparable to the thickness decline in patients with Alzheimer disease. 34 In the current study, we found no association between remote changes in cortex or connecting fiber tracts and clinical outcome (supplementary results, table e-2). This might relate to several factors.…”
Section: Figure 4 Influence Of Infarct Cavitationcontrasting
confidence: 51%
“…We also evaluated correlations between DTI measures at different depths: there were generally high correlations between midcortical measurements and the deepest WM layer for FA (0.43), MD (0.63) and cPDD (0.33). Given that our DWI scans have a resolution of 3 mm and mean cortical thickness averages about 2.5 mm [43,44], there should have been minimal overlap between the measurements at these two depths. However, the two measurements will not be independent given the smoothness of the DWI images, digital filtering and residual joint misregistration.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it can assess these parameters of brain morphology and their contribution independ ently from each other and is not so sensitive to image registration as it computes the morphometric parameters in native space. [16][17][18] To the best of our knowledge, only 2 studies have used the SBA approach in OCD samples to study gyrification, volume, surface area and thickness at the same time. 19,20 Venkatasubramanian and colleagues 19 applied SBA by using the automatic FreeSurfer software and provided first evidence of altered volume, surface area and thickness in a number of different regions comprising the ACC, OFC and occipital cortex in medication-naive patients with OCD.…”
Section: J Psychiatry Neurosci 2017;42(6)mentioning
confidence: 99%